Gemeinwohl durch Wettbewerb? : Berichte und Diskussionen auf der Tagung der Vereinigung der Deutschen Staatsrechtslehrer in Graz vom 7. bis 10. Oktober 2009. - Peters, Anne (De Gruyter, 2010)
This volume contains essays and discussions from the Conference of the Association of German Constitutional Law Instructors held October 7 - 10, 2009 in Graz.
Verzeichnis der Mitglieder der Vereinigung der Deutschen StaatsrechtslehrerSatzung der Vereinigung.
Keywords: Administrative law.; Constitutional law.; Law.; Law - Non-U.S.; Law, Politics & Government.; Law - Europe, except U.K.; Electronic books.